Kepadatan Populasi dan Distribusi Ukuran Kerang Contradens sp. di Perairan Tanjung Mutiara Danau Singkarak, Sumatera Barat - Misren Ahyuni; - Izmiarti; - Afrizal (Jurnal Biologi Universitas Andalas, 2014)
The study about population density and shell size distribution of clam Contradens sp. in Tanjung Mutiara Singkarak Lake, West Sumatra has been conducted on July 2013. This study used stratified purposive sampling method. Sampling site was decided into 3 locations based on human activities, 3 depth strata in each location; <5m, 5-10m and >10-15m. The clams were collected using “dauah” (traditional tool to catch shellfish), 3 sampling plots for each stratum. The result showed that the highest average population density (2.596 ind/m2) was found in location III followed location II (0.055 ind/m2) and location I (0.155 ind/m2). Based on strata, the highest average population density (1.941 ind/m2) was at >10-15m depth, there was no clam found at <5m depth. The largest clam concentrated  at >10-15m depth in location III (without human activity area) whereas small to medium clam concentrated at 5-10m depth.Keywords: clam, Contradens sp., population density, size distribution, Singkarak Lake.